Evaluating performance of our clinical biochemistry laboratory by application of sigma metrics & other quality indicators- A pilot study (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Ensuring quality of laboratory services is the need of the hour in the field of health care. Six Sigma is a new management philosophy that seeks a nonexistent error rate, keeping in mind that we aimed to gauge our laboratory performance by sigma metrics. Internal quality control (QC) data was analysed retrospectively over a period of 6 month from February 2015 to July 2015. Laboratory mean, SD and coefficient of variation were calculated for all the parameters. We studied parameters which are in scope of NABL of our Laboratory. Quality assessed on sigma scale with a bench mark for minimum process performance of 3sigma and a goal for world class quality of 6 Sigma (σ).  Satisfactory sigma value (>6) were elicited for ALP & Total Bilirubin. We have achieved sigma metrics of the range 3-5 for   Albumin, AST, ALT, Total Cholesterol, Creatinine, Total Protein, Uric Acid, Glucose and Direct Bilirubin signifying acceptable laboratory performance with a scope for improvisation. Blood Urea performed poorly on the sigma scale with